The globalization of advertising : agencies, cities and spaces of creativity - Faulconbridge, James R. (Routledge, 2011)
This text unpacks the contemporary structure and spatial organization of global advertising agencies and reveals how global agencies operate as transnationally integrated organizations. It focuses on how the role of New York, Detroit and Los Angeles in advertising work has changed radically over the years